2016
DOI: 10.1016/j.jtcvs.2015.09.100
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events in contemporary continuous-flow left ventricular assist devices: A multi-institutional comparison shows significant differences

Abstract: In this pooled analysis, a trend was found for higher incidence of percutaneous driveline infections in patients treated with the HMII; a higher incidence of stroke and time-related cumulative risk of any infection and stroke was found in patients treated with the HVAD, which was independently associated with higher stroke risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 25 publications
5
83
3
3
Order By: Relevance
“…Despite the low INR target, we demonstrated no increase in the rate of thromboembolic events. The incidence of both PT and IS was lower than the incidences reported by Starling et al, 18 Stulak et al 19 and McIlvennan et al, 3 and comparable to the incidence reported in the PREVENtion study. 4 Data on the safety, risks, and hemostatic profile of HMII patients in whom AT can be safely discontinued are scarce.…”
Section: Survival and Mortalitysupporting
confidence: 67%
See 1 more Smart Citation
“…Despite the low INR target, we demonstrated no increase in the rate of thromboembolic events. The incidence of both PT and IS was lower than the incidences reported by Starling et al, 18 Stulak et al 19 and McIlvennan et al, 3 and comparable to the incidence reported in the PREVENtion study. 4 Data on the safety, risks, and hemostatic profile of HMII patients in whom AT can be safely discontinued are scarce.…”
Section: Survival and Mortalitysupporting
confidence: 67%
“…The median time until the first bleeding event after discharge that led to rehospitalization was 8.5 [IQR: 5,19] the bleeding rate was significantly lower after AT cessation than before cessation (0.09 eppy vs. 3.58 eppy, P<0.001). The mean INR after AT cessation during follow-up was 1.0±0.2.…”
Section: Advance Publication By-j-stagementioning
confidence: 99%
“…(10) Prior studies have identified patient and device-specific stroke risk factors, including female gender, infection, atrial fibrillation, hypertension, anticoagulant levels, duration of LVAD support, and LVAD type. (1,3,11,12) However, given the small number of events, these studies had limited power to test a large number of contributing factors in a multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, despite advances in device longevity and patient survival, stroke rates have not improved significantly, and may even be increasing with some newer generation devices. (1)…”
Section: Introductionmentioning
confidence: 99%
“…However, in a multi-institution pooled analysis, a trend was found for higher incidence of driveline infections in patients with Heartmate II, and a higher incidence of stroke was found in patients treated with the HeartWare VAD. 62 We continue to struggle to decide when to implant a VAD in the less sick cohort of patients with ambulatory severe HF, especially those who are not yet on inotropes. The recently published Risk Assessment and Comparative Effectiveness of Left Ventricular Assist Device and Medical Management in Ambulatory Heart Failure Patients (ROADMAP) observational study suggested benefit in terms of survival and quality of life despite increase in adverse events in patients who received a VAD compared with those treated with medical therapy.…”
Section: Ventricular Assist Devicesmentioning
confidence: 99%